Associations of mindfulness with adolescent outcomes and sexuality. (June 2020) - Leavitt, Chelom E.; Allsop, David B.; Busby, Dean M.; Driggs, Shayla M.; Johnson, Heather M.; Saxey, Matthew T.
Abstract: Introduction: Using an online survey, we evaluated how adolescent trait and state mindfulness was associated with positive adolescent outcomes in non-sexually active and sexually active adolescents. Additionally, we evaluated a newly developed measure, the Sexual Mindfulness Measure (SMM), with adolescents. Methods: We asked 2000 U.S. adolescents (half boys/girls; 1/3 low, medium, and high incomes) aged 13–18 (one group 13–15, another 16–18) about trait mindfulness, sexual state mindfulness, and adolescent outcomes. Using Confirmatory Factor Analysis and structured equation modeling, we evaluated the reliability and validity of the SMM and its associations with adolescent outcomes. Results: Using a trait mindfulness measure, we found that mindful adolescents with no sexual experience, showed positive associations with self-efficacy, body-esteem, and disclosure with both fathers and mothers. Evaluating adolescents who were sexually active, we confirmed that the SMM had a two-factor structure and demonstrated acceptable reliability for both male and female adolescents. We found that the SMM was associated with positive sexual attitudes, body image, self-efficacy, and disclosure to parents above and beyond trait mindfulness. Conclusions: Trait mindfulness was associated with positive self-assessments and parental disclosure. The SMM provided an important assessment of how sexually active adolescents' ability to remain aware and non-judgmental during sexual experiences may be positively associated with outcomes such as sexual consent, positive body image, self-efficacy, disclosure to parents, and negatively associated with sexual shame and sexual anxiety above and beyond trait mindfulness.